The role of occupational segregation for gender-specific employment patterns in West Germany - Lydia Malin (ZBW - Leibniz Information Centre for Economics, 2020)
Despite increasing educational attainment and greater labor market participation of women in the last decades, occupational segregation and gender differences in employment patterns remain stable. While men continue to have fairly stable employment patterns, women's occupational trajectories are more affected by discontinuity and part-time work. Previous research on gender inequality in labor markets (LM) focused on individual- and macro-level influences on e.g. female labor supply and wages. This study adds to and extends previous research by focusing on men's employment patterns in occupations with different gender-types. Doing so, this analysis contributes to disentangle individual and contextual influences by comparing typical employment patterns of men in female-typical occupations with those of their female colleagues and those of men in male-typical occupations. By this means, the aim of this study is to detect the contribution of occupational settings to gender differentiation in employment patterns. Drawing on data from the German National Educational Panel Study (NEPS), I use sequence clustering to detect different types of employment patterns and following multinomial logistic regressions on cluster membership. The results show that employment patterns differ by gender and type of occupation. Most men do have continuous fulltime employment patterns, even in female occupations. However, men in female occupations are significantly more likely to have work interruptions for further education and part-time dominated employment trajectories compared to men in male-typical occupations.
Keywords: J; 330; Career patterns; employment trajectories; work histories; gender-atypical occupations; sequence analysis; optimal matching; cluster analysis